Anatomy and ultrastructure of the ventral pharyngeal organs of Saccocirrus (Saccocirridae) and Protodriloides (Protodriloidae fam. n.) with remarks on the phylogenetic relationships within Protodrilida (Annelida: Polychaeta - Purschke, G?.; Jouin, C. (Journal of Zoology, London, 1988)
General anatomy and ultrastructure of the ventral pharyngeal organs were investigated in Saccocirrus krusudensis, Protodriloides chaetifer and P. symbioticus. Saccocirrus papillocercus, a species without a ventral pharyngeal organ, was included for comparison. The two genera show homologous similarities in their pharynges: bulbus muscle composed of transverse muscle fibres and interstitial cells, those cells with small cell bodies and processes containing prominent tonofilaments which are orientated dorsoventrally and connect the bulbus epithelium with the investing muscle; bulbus muscle fibres circomyarian with nuclei and mitochondria located basally, investing muscle also with interstitial cells, which lack tonofilaments; oesophagus surrounded by gland cells opening into the pharynx. Most likely, a ventral pharynx with these characters was already present in the stem species of Saccocirridae, Protodriloidae fam. n. and Protodrilidae and evolutionary processes led to several changes: a tongue-like organ with a prominent tip and supporting elements is a synapomorphic character of Protodrilus and Saccocirrus; the pharyngeal organ is reduced to stomodeal pouches and salivary glands in S. papillocercus and completely lost in Astomus taenioides. These results and data from previous studies are summarized in a tentative phylogenetic dendrogram and allow the introduction of a new family, Protodriloidae.
World Polychaeta Database (WPolyDb)